Practice as Research in the Arts (and Beyond) - Nelson, Robin. author. aut Link
XXI, 196 p. 15 illus.
Keywords: This project addresses the contexts of Practice as Research and how to undertake it. This second iteration updates thinking and practices but sustains a direct and clear approach on how to become a practitioner-researcher. New features include an extension of range “beyond” the arts and a case for intra-disciplinarity in Practice Research as an influence in the formation of the “future university”. A comparison is made between Artistic Research and Practice Research recognizing that research through practices with being-doing-knowing is central to both. Acknowledging the current crisis in legitimation, a broad view is taken of how things might be known by an onto-epistemology for the twenty-first century foregrounding the bodymind but sustaining rationality and community by way of Other/other dialogic exchange. Perspectives from around the world in Part II offset the more Eurocentric emphasis in Part I.